Strategies and tools for the biotechnological valorization of glycerol to 1, 3-propanediol: challenges, recent advancements and future outlook - Agrawal, Deepti; Budakoti, Mridul; Kumar, Vinod (Elsevier, 2023)
Global efforts towards decarbonization, environmental sustainability, and a growing impetus for exploiting renewable resources such as biomass have spurred the growth and usage of bio-based chemicals and fuels. In light of such developments, the biodiesel industry will likely flourish, as the transport sector is taking several initiatives to attain carbon-neutral mobility. However, this industry would inevitably generate glycerol as an abundant waste by-product. Despite being a renewable organic carbon source and assimilated by several prokaryotes, presently realizing glycerol-based biorefinery is a distant reality. Among several platform chemicals such as ethanol, lactic acid, succinic acid, 2, 3-butanediol etc., 1, 3-propanediol (1, 3-PDO) is the only chemical naturally produced by fermentation, with glycerol as a native substrate. The recent commercialization of glycerol-based 1, 3-PDO by Metabolic Explorer, France, has revived research interests in developing alternate cost-competitive, scalable and marketable bioprocesses. The current review outlines natural glycerol assimilating and 1, 3-PDO-producing microbes, their metabolic pathways, and associated genes. Later, technical barriers are carefully examined, such as the direct use of industrial glycerol as input material and genetic and metabolic issues related to microbes alleviating their industrial use. Biotechnological interventions exploited in the past five years, which can substantially circumvent these challenges, such as microbial bioprospecting, mutagenesis, metabolic, evolutionary and bioprocess engineering, including their combinations, are discussed in detail. The concluding section sheds light on some of the emerging and most promising breakthroughs which have resulted in evolving new, efficient, and robust microbial cell factories and/or bioprocesses for glycerol-based 1, 3-PDO production.
Keywords: Glycerol; 1,3 - propanediol; Genetic interventions; Bioprospecting; Process intensification; Adaptive laboratory evolution; Mutagenesis; Fermentation